The Quest for Legal Protection of Men From Domestic Violence - Jonathan Delight Ofungi (Uganda Christian University, 2024)
The prevailing discourse surrounding domestic violence often focuses on female victims, yet an increasing body of research and anecdotal evidence highlights the prevalence of male victims. This abstract delves into the legal dimensions of this often-overlooked phenomenon, examining the challenges and opportunities within the legal framework for addressing domestic violence against men. Through a comprehensive review of existing literature and legal precedents, this paper explores the barriers men face in seeking legal redress, including societal stigmas, gender biases within the justice system, and the lack of tailored support services. Additionally, it investigates the efficacy of current legal remedies in providing protection and justice for male victims, while also considering potential reforms to enhance their access to justice. By shedding light on the legal complexities surrounding domestic violence against men, this abstract contributes to a more inclusive and equitable understanding of intimate partner violence within the legal sphere.